2015
DOI: 10.1103/physrevd.91.055001
|View full text |Cite|
|
Sign up to set email alerts
|

Probing Wilson loops in AdS/QCD

Abstract: We use AdS/QCD to analyze the quark and gluon scalar and pseudo-scalar condensates around static color sources described by a circular Wilson loop. We also derive the static dipole-dipole interactions between rectangular Wilson loops in AdS/QCD and discuss their relevance for static string interactions in QCD at strong coupling.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Given a catalogue of galaxies with shear and redshift estimates, there exist many ways to extract the lensing information that is required to constrain the underlying cosmological parameters that describe our Universe at its largest scales. The central approach adopted by the above-mentioned surveys starts with the measurement of a two-point summary statistics, either the configuration-space correlation function (as in Kilbinger et al 2013;Hildebrandt et al 2017;Troxel et al 2018;Hildebrandt et al 2018) or the Fourier-space power spectra (as in Liu et al 2015a;Köhlinger et al 2017;Hikage et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Given a catalogue of galaxies with shear and redshift estimates, there exist many ways to extract the lensing information that is required to constrain the underlying cosmological parameters that describe our Universe at its largest scales. The central approach adopted by the above-mentioned surveys starts with the measurement of a two-point summary statistics, either the configuration-space correlation function (as in Kilbinger et al 2013;Hildebrandt et al 2017;Troxel et al 2018;Hildebrandt et al 2018) or the Fourier-space power spectra (as in Liu et al 2015a;Köhlinger et al 2017;Hikage et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these articles, the effect of strong magnetic fields is also studied on the properties of ρ meson [71], B meson [72,73], charmonium [9,16,17,74] and bottomonium states [74,75]. A lot of work has also been done without taking the effect of magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, WL peak counts are sensitive to changes of shape of the mass function. In the literature, it has been shown that peak counts alone constrain cosmology more strictly than two-point-correlation functions and the combination of both statistics improves the constraints (Dietrich & Hartlap 2010;Liu, J. et al 2015a). Applications to observational data are also multiple.…”
Section: Introductionmentioning
confidence: 99%